2000
DOI: 10.1111/1467-8462.00152
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern and Determinants of Intra‐Industry Trade in Australian Manufacturing

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
6
18
0
5
Order By: Relevance
“…Another important factor that is considered directly or indirectly is the product differentiation. it is worth mentioning that products can be differentiated in three main forms: horizontal, vertical and technological differentiation (Sharma 1999). intra-industry differences in the iiT can be affected by all three types of differentiation and specifically it is expected that the relationship between the iiT and the country-level product differentiation (cPD) will be positive.…”
Section: Review Of the Theoretical And Empirical Literaturementioning
confidence: 99%
“…Another important factor that is considered directly or indirectly is the product differentiation. it is worth mentioning that products can be differentiated in three main forms: horizontal, vertical and technological differentiation (Sharma 1999). intra-industry differences in the iiT can be affected by all three types of differentiation and specifically it is expected that the relationship between the iiT and the country-level product differentiation (cPD) will be positive.…”
Section: Review Of the Theoretical And Empirical Literaturementioning
confidence: 99%
“…Since large economies can readily gain from economies of scale, they can make use of benefits resulting from their large domestic market easily and so, have higher extent of IIT (Sharma, 2000). The ratio of pharmaceutical turnover (total sales) (TUR i ) to the number of pharmaceutical companies (MS i ) are used to compute economies of scale (ES i ) for Iran’s pharmaceutical industry, in this research.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Leitão and Faustino (2007) also found a negative relationship between FDI with horizontal IIT. However, the study by Sharma (2000) on the pattern and determinants of IIT in the Australian manufacturing sector showed that FDI has a negative significant effect on IIT due to increased competition. Thus, these findings indicate that the effect of FDI on IIT is inconclusive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study adopted the method used by Hu and Ma (1999), Sharma (2000), and Veeramani (2007) which uses the weighted distance as a proxy for geographical distance between trade partners. This is to avoid overestimating the internal or external distance ratio, which will result in an upward bias in the border effect estimate: org/10.15405/epsbs.2016.11.02.25 eISSN: 2357-1330 …”
Section: Geographical Distancementioning
confidence: 99%